2002
DOI: 10.1603/0022-2585-39.1.198
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofBorrelia burgdorferiSensu Lato Infection Among Rodents and Host-Seeking Ticks in South Carolina

Abstract: Tissues of rodents and host-seeking adult ticks collected in the Piedmont, Sandhills, Coastal Plain, and Coastal Zone of South Carolina were cultured in attempts to isolate Borrelia burgdorferi (Johnson, Schmid, Hyde, Steigerwalt & Brenner), the etiologic agent of Lyme disease. An exploratory, tree-based statistical analysis was used to identify ecological variables that were associated with spirochete infection among rodents and ticks. Spirochetes were isolated from tissues of 71 rodents: 22 (69%) of 32 easte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 59 publications
(63 reference statements)
3
23
0
Order By: Relevance
“…Although they are much less aggressive in biting humans in this region, I. scapularis ticks are also infected with B. burgdorferi sensu lato strains and could occasionally transmit them to people. The prevalence of infection in adult I. affinis ticks in Florida based on PCR testing (31%) was similar to that found in South Carolina (25.7%) by using culture isolation (11). However, this tick species is not known to bite humans and probably is important only in the enzootic transmission of the spirochete among small mammals, which are the preferred hosts for the immature tick stages (10).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Although they are much less aggressive in biting humans in this region, I. scapularis ticks are also infected with B. burgdorferi sensu lato strains and could occasionally transmit them to people. The prevalence of infection in adult I. affinis ticks in Florida based on PCR testing (31%) was similar to that found in South Carolina (25.7%) by using culture isolation (11). However, this tick species is not known to bite humans and probably is important only in the enzootic transmission of the spirochete among small mammals, which are the preferred hosts for the immature tick stages (10).…”
Section: Discussionsupporting
confidence: 70%
“…Only 1.3% in South Carolina were infected, based on BSK culture results (11). The present study also identified a very high B. burgdorferi sensu lato infection prevalence (85%) among small mammals from two sites near the Atlantic Coast in northeast Florida.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…B. burgdorferi has been detected in 35 to 50% of I. scapularis ticks in the northeastern states (4) but is rarely found in ticks in the southern United States (5)(6)(7)(8)(9). In contrast, 63% of I. affinis ticks were found to have Borrelia DNA by PCR (10).…”
mentioning
confidence: 99%
“…Primarily as a result of Lyme disease, the seasonality and life cycle of I. scapularis have been well studied in the northeastern and central U.S.; however, less is known about the biology of this tick in the southern U.S. (Clark et al 2002, Goddard 1992, 1993, Oliver 1993, Mackay & Foil 2005, Goddard & Piesman 2006. For example, in a 10-year survey of human-biting ticks in Mississippi, I. scapularis was responsible for 9.2% of reported human tick bites, making it the fourth most Article common tick found on humans in Mississippi (Goddard 2002), and in Florida, Georgia and South Carolina, I. scapularis was commonly collected in several studies (Felz et al 1996, Cilek & Olson 2000.…”
Section: Introductionmentioning
confidence: 99%